Nothing to envy : ordinary lives in North Korea - Demick, Barbara (Spiegel & Grau, 2009)
Follows the lives of six North Koreans over fifteen years, a chaotic period that saw the rise to power of Kim Jong Il and the devastation of a famine that killed one-fifth of the population, illustrating what it means to live under the most repressive totalitarian regime today.